2015
DOI: 10.1103/physreve.92.022719
|View full text |Cite
|
Sign up to set email alerts
|

Detection of short single-strand DNA homopolymers with ultrathinSi3N4nanopores

Abstract: A series of nanopores with diameters ranging from 2.5 to 63 nm are fabricated on a reduced Si3N4 membrane by focused ion beam and high energy electron beam. Through measuring the blocked ionic currents for DNA strands threading linearly through those solid-state nanopores, it is found that the blockade ionic current is proportional to the square of the hydrodynamic diameter of the DNA strand. With the nanopore diameter reduced to be comparable with that of DNA strands, the hydrodynamic diameter of the DNA beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 44 publications
5
29
0
Order By: Relevance
“…However, a much more attractive idea is to use a non-Abelian discrete family symmetry, which is softly broken in the dark sector. In particular, ∆ (27) [19,20,21,22,23] has been shown to be useful in achieving the goal of having scotogenic Dirac neutrino masses with a mixing pattern [24,25,26] called cobimaximal [27,28,29,30,31,32], i.e. θ 23 = π/4 and δ CP = ±π/2, which is consistent with present neutrino oscillation data [33] for δ CP = −π/2.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, a much more attractive idea is to use a non-Abelian discrete family symmetry, which is softly broken in the dark sector. In particular, ∆ (27) [19,20,21,22,23] has been shown to be useful in achieving the goal of having scotogenic Dirac neutrino masses with a mixing pattern [24,25,26] called cobimaximal [27,28,29,30,31,32], i.e. θ 23 = π/4 and δ CP = ±π/2, which is consistent with present neutrino oscillation data [33] for δ CP = −π/2.…”
Section: Introductionsupporting
confidence: 70%
“…[6,23], the interplay between U (1) χ and ∆ (27) is used for restricting the interaction terms among the various fermions and scalars. The irreducible representations of ∆ (27) and their character table are given in Ref. [19].…”
Section: Outline Of Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, all triplets considered for our ARBD simulations maintained the same base stacking pattern, Figure 4a. In comparison to the limited number of experimental studies that reported ionic current blockades from DNA homopolymers in solid-state nanopores, our calculations are in partial agreement with the data from Drndic, Radenovic and Chen labs 4648 but disagree with the blockade ranking reported by Kim and co-workers 29 . The lack of consensus about the qualitative ranking of experimental current blockades may in fact indicate their high sensitivity to the nanopore size and membrane material.…”
Section: Resultssupporting
confidence: 59%
“…The current blockades from a DNA fragment in MspA were found to be modulated by at least four nucleotides 12,14 , with the current modulation amplitudes in no obvious relation to the current amplitudes produced by DNA of uniform sequences 45 . Similarly, several different rankings of blockade currents from DNA homopolymers have been reported for solid-state nanopores 29,4648 These differences may arise from the distinct conformations that DNA adopts within the constriction of different nanopores as well as the differences in ion distributions due the charge and shape of the nanopore walls. Most importantly, the sensitivity of ionic current blockades to the nucleotide sequence of DNA in solid-state nanopores remains to be determined, as well as the conditions that would be optimal for sequence determination.…”
Section: Introductionmentioning
confidence: 90%